A Logic Model Framework for Planning an International Refugee Health Research, Evaluation, and Ethics Committee. Issue 5 (September 2022) - Payton, Colleen; Kumar, Gayathri S.; Kimball, Sarah; Clarke, Sarah K.; AlMasri, Ibrahim; Karaki, Fatima M.
Collaborative approaches to supporting the health of refugees and other newcomer populations in their resettlement country are needed to address the complex medical and social challenges they may experience after arrival. Refugee health professionals within the Society of Refugee Healthcare Providers (SRHP)—the largest medical society dedicated to refugee health in North America—have expressed interest in greater research collaborations across SRHP membership and a need for guidance in conducting ethical research on refugee health. This article describes a logic model framework for planning the SRHP Research, Evaluation, and Ethics Committee. A logic model was developed to outline the priorities, inputs, outputs, outcomes, assumptions, external factors, and evaluation plan for the committee. The short-term outcomes include (1) establish professional standards in refugee health research, (2) support evaluation of existing refugee health structures and programs, and (3) establish and disseminate an ethical framework for refugee health research. The SRHP Research, Evaluation, and Ethics Committee found the logic model to be an effective planning tool. The model presented here could support the planning of other research committees aimed at helping to achieve health equity for resettled refugee populations.